Analysis of Plant Seed Distribution Activities by Immigration Polytechnic Cadets in Car Free Day Activities in Tangerang - Teuku Chrismon Shavirko; Sri Kuncoro Bawono (Polteknik Imigrasi, 2020)
The purpose of carrying out the activity of distributing plant seeds by the Immigration Polytechnic Cadets with the Class I Non TPI Tangerang Immigration Office in this car free day activity is a form of concern for the surrounding environment, especially the people of Tangerang City. The activity, which was carried out with the theme